2014
DOI: 10.1074/jbc.m113.499517
|View full text |Cite
|
Sign up to set email alerts
|

The MF6p/FhHDM-1 Major Antigen Secreted by the Trematode Parasite Fasciola hepatica Is a Heme-binding Protein

Abstract: Background:The mechanisms involved in heme handling in trematodes are poorly understood. Results: The biochemical and functional characteristics of a new family of small proteins (MF6p/FhHDM-1) secreted by Fasciola and other trematodes are reported. Conclusion:The Fasciola MF6p/FhHDM-1 major antigen is a heme-binding protein. Significance:Our results provide new insights into the biology of hematophagous trematodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 53 publications
2
39
1
Order By: Relevance
“…has not yet been convincingly demonstrated; however, because of its ability to bind to lipopolysaccharide (LPS) and to prevent LPS-induced inflammation in mice (6) as well as its ability to suppress antigen processing and presentation in macrophages (9), it has been suggested that the protein may favor parasite survival by suppressing the host immune response (10). Nevertheless, we previously suggested that the protein may play a role in heme homeostasis on the basis of its heme-binding nature and the fact that it accumulates in several internal fluke tissues, mainly parenchymal cells, vitellaria, testicular tubules, and the basal lamina under the tegument (7). To gain further insight into the mode of action of MF6p/HDM proteins, we have carried out a detailed study of the binding characteristics of these proteins in relation to heme and LPS.…”
Section: The Physiological Role Of Mf6p/fhhdm-1 In the Parasitementioning
confidence: 99%
See 2 more Smart Citations
“…has not yet been convincingly demonstrated; however, because of its ability to bind to lipopolysaccharide (LPS) and to prevent LPS-induced inflammation in mice (6) as well as its ability to suppress antigen processing and presentation in macrophages (9), it has been suggested that the protein may favor parasite survival by suppressing the host immune response (10). Nevertheless, we previously suggested that the protein may play a role in heme homeostasis on the basis of its heme-binding nature and the fact that it accumulates in several internal fluke tissues, mainly parenchymal cells, vitellaria, testicular tubules, and the basal lamina under the tegument (7). To gain further insight into the mode of action of MF6p/HDM proteins, we have carried out a detailed study of the binding characteristics of these proteins in relation to heme and LPS.…”
Section: The Physiological Role Of Mf6p/fhhdm-1 In the Parasitementioning
confidence: 99%
“…Previous studies (6), including a study by our research group (7), have identified and cloned a small protein (molecular mass, 7.8 kDa) that is abundant in somatic and secretory antigens (SAs) 3 of F. hepatica and that is recognized by the MF6 monoclonal antibody (mAb). This protein was initially erroneously identified as Fasciola hemoglobin (8), and it was later renamed FhHDM-1 on the basis of its homology with cathelicidin-like host defense peptides (6,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the physiological roles of MF6p/HDMs in trematode parasites have not been clearly established, several studies suggested two interesting biological functions of this family of proteins. The molecules act as heme scavengers and transporters to maintain heme homeostasis in trematode parasites, indicating an essential role in parasite survival by detoxifying the toxic free form [9,14]. Their ability to bind to LPS and prevent LPS-induced inflammation in mice as well as their ability to suppress antigen processing and presentation in macrophages also suggested an immunomodulatory role in suppressing host immune response, which facilitated prolonged parasite survival in the hosts [10-13, 36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies investigating FhMF6p/ HDM suggested a role in host immune modulation [10][11][12][13]. Moreover, the increased interest in this molecule has been attributed to its heme-binding ability, and its role as a heme scavenger and transporter to maintain heme homeostasis in trematode parasites [9,14]. The hemescavenging ability is essential for the survival of bloodfeeding trematodes since large amount of heme, which is toxic as a free form, are released from the catabolism of host erythrocytes [15].…”
Section: Introductionmentioning
confidence: 99%